Synthesis of lutetium hydrides at high pressures - Yuan-Ao Peng; Han-Yu Wang; Fu-Hai Su; Pu Wang; Hai-An Xu; Lin Liu; Lun-Xuan Yu; Ross T. Howie; Wan Xu; Eugene Gregoryanz; Xiao-Di Liu (Matter and Radiation at Extremes)
High-pressure synthesis of lutetium hydrides from molecular hydrogen (H2) and lutetium (Lu) is systematically investigated using synchrotron X-ray diffraction, Raman spectroscopy, and visual observations. We demonstrate that the reaction pathway between H2 and Lu invariably follows the sequence Lu ⟶ LuH2 ⟶ LuH3 and exhibits a notable time dependence. A comprehensive diagram representing the formation and synthesis of lutetium hydrides as a function of pressure and time is constructed. Our findings indicate that the synthesis can be accelerated by elevated temperature and decelerated by increased pressure. Notably, two critical pressure thresholds at ambient temperature are identified: the synthesis of LuH2 from Lu commences at a minimum pressure of ∼3 GPa, while ∼28 GPa is the minimum pressure at which LuH2 fails to transform into LuH3 within a time scale of months. This underscores the significant impact of temporal factors on synthesis, with the reaction completion time increasing sub-linearly with rising pressure. Furthermore, the cubic phase of LuH3 can be obtained exclusively through compressing the trigonal LuH3 phase at ∼11.5 GPa. We also demonstrate that the bandgap of LuH3 slowly closes under pressure and is noticeably lower than that of LuH2.